Evaluation of Chili Nazla IPB as An Ornamental Chilli for Releasing Variety - Abdul Hakim; Muhamad Syukur; Sobir; Awang Maharijaya; Syarifah Iis Aisyah; Dewi Sukma; Arya Widura Ritonga; Muhammad Ridha Alfarabi Istiqlal; Sulassih; Bagas Akmala Putra; Arum Sholikhah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Chili (Capsicum annuum L.) exhibits a wide range of variations in terms of crown shape, fruit shape, fruit color, leaf color, leaf shape, and taste. While chili is commonly known as a food plant, it also serves as an attractive ornamental plant. Specifically, ornamental chili plants are desired to possess specific traits, such as compact growth, high fruit yield, and a variety of fruit colors within a single plant. This study aims to comprehensively describe the quantitative and qualitative superiority of the Nazla IPB variety in terms of its characteristics. The research was conducted in the Leuwikopo Darmaga experimental garden's greenhouse, located in Bogor, utilizing a randomized complete block design with four replications. The Nazla IPB variety, which is an open-pollinated (OP) cultivar, stands out due to its short plant height, ranging from 17.83 to 26.42 cm, making it highly suitable for ornamental purposes. Furthermore, the chili plants of the Nazla IPB variety possess a compact crown shape, enhancing their visual appeal, coupled with their short stature (ranging from 21.83 to 26.69 cm). The primary distinguishing features of the ornamental chili variety Nazla IPB include: 1) the color of the leaves, which transition from green (Green 137 C) to purple (Purple N186 A); 2) the black color of the young chili fruit (Black 203 A); 3) the fruit shape of Nazla IPB, which can be described as moderately triangular; and 4) the fruit undergoes a color transformation from black to dark green and finally to red. Nazla IPB has potential to serve as an attractive decorative plant option.